Study on the synthesis of a macroporous ethylacrylate‐divinylbenzene copolymer, its conversion into a bi‐functional cation exchange resin and applications for extraction of toxic heavy metals from wastewater. Issue 4 (15th January 2013) - Ali, Syed Wasim; Waqar, Farhat; Malik, Muhammad Arif; Yasin, Tariq; Muhammad, Bashir
Abstract Macroporus ethylacrylate‐divinylbenzene copolymers were synthesized by suspension polymerization using diethyl phthalate and n‐heptane as diluent. A hydrolysis study revealed that conversion of esters into carboxylic acid groups was dependent on three factors: (1) crosslinkage: increases with a decrease in crosslinkage, (2) reagent: sulfuric acid>aqueous NaOH>NaOH in a 1 : 1 water to ethylene glycol, and (3) pore volume (PV): highest when PV was ∼ 0.7 mL g−1. Sulfuric acid hydrolyzed ester to COOH and introduced SO3H on phenyl rings, thus producing a bi‐functional resin. The functional groups were verified by IR spectroscopy and quantified by acid–base titration. The bi‐functional resin's capacity for toxic heavy metals in water samples was 12.51, 10.43, 9.43, 13.21, and 11.12 mg g−1 for Cu, Cd, Ni, Pb, and Zn, respectively and the recoveries exceeded >95% in range of pH 2–8, showing that it is suitable for water purification. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013